Penggunaan Larutan Fermentasi Kulit Singkong dan Garam Terhadap Masa Simpan Filet Nila Merah Berdasarkan Jumlah Mikroba Pada Penyimpanan Suhu Rendah - Shally Auliyatul Hakim; Evi Liviawaty; Subiyanto Subiyanto; Rusky Intan Pratama (Jurnal Perikanan Unram, 2024)
This research was conducted to analyze the best salt concentration in the cassava peel fermentation solution to extend the shelf life of red tilapia fillets based on the number of microbes during low temperature storage (5°-10°C). Soaking red tilapia fillets using fermented cassava peel solution with various added salt concentrations consisting of 4 treatments, namely 0% (control), 2%, 3% and 4%, soaking for 30 minutes for each fillet according to the treatment. The parameters observed were the number of bacterial colonies and the degree of acidity (pH), each parameter was carried out in duplicate. For concentrations of 0%, observations were made on days 1, 3, 6, 7, 8, 9, while for concentrations of 2%, 3% and 4%, observations were made on days 1, 4, 7, 8, 9, 10, 11 and 12. The results of the study showed that soaking red tilapia filets using fermented cassava skin solution, namely adding 3% salt concentration, had the best effect on shelf life during low temperature storage with an acceptance limit of up to the 11th day with TPC value is 2,5 x 106 and a pH value is 6,5.